2008
DOI: 10.1111/j.1751-1097.2007.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy of Nonmelanoma Skin Cancer with Topical Hypericum perforatum Extract—A Pilot Study

Abstract: Hypericin, the photoactive compound of Hypericum perforatum, is probably the most powerful photosensitizer found in nature. This compound has shown high potency in the photodynamic treatment of tumor cells. However, there is only limited knowledge regarding the photodynamic effect of hypericin on nonmelanoma skin cancer cells. The aim of this prospective study was to investigate the efficacy of photodynamic therapy with topical application of an extract of H. perforatum in actinic keratosis, basal cell carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Clinical trials have been performed to treat squamous cell carcinoma and basal cell carcinoma [77] but the results are unsatisfactory to date. Studies aimed at optimization and enhancement of dosage, drug and light delivery, and preparation of tested area have been undertaken [78]. …”
Section: Photosensitizer Typesmentioning
confidence: 99%
“…Clinical trials have been performed to treat squamous cell carcinoma and basal cell carcinoma [77] but the results are unsatisfactory to date. Studies aimed at optimization and enhancement of dosage, drug and light delivery, and preparation of tested area have been undertaken [78]. …”
Section: Photosensitizer Typesmentioning
confidence: 99%
“…Although potentially promising from its properties (high tumour selectivity and efficiency) and proved in experiments with mice (3)(4)(5), only a few clinical data concerning the treatment of (pre)cancerous lesions of the skin exist. Hypericin was applied successfully on human skin carcinomas BCC (basal cell carcinoma) and SCC (squamous cell carcinoma) (6,7), but an extract of Hypericum perforatum, used in a clinical pilot study on actinic keratoses, BCC and Bowen's disease, showed only partial success (8). The results, however, are difficult to evaluate, since an extract of the whole plant may contain also inhibitory compounds.…”
Section: Introductionmentioning
confidence: 91%
“…A prospective pilot study by Kacerovská et al investigated the use of an extract of H. perforatum in combination with photodynamic therapy for BCCs, actinic keratoses, and Bowens disease (carcinoma in situ) [16]. A total of 34 patients were enrolled, 21 of which had BCCs.…”
Section: Botanical Agents Studied In Humans and Animals (Tables 1 mentioning
confidence: 99%
“…They found complete clinical response for 28% of superficial BCC patients, and only partial remission was seen in nodular BCC patients [16]. By histology, a complete disappearance of cancer cells was found in 11% of the superficial BCCs [16]. All patients in the study complained of pain and burning during irradiation.…”
Section: Botanical Agents Studied In Humans and Animals (Tables 1 mentioning
confidence: 99%